Phytochemical composition, antioxidant activities and anti‐obesity potential of selected vegetables as affected by drying methods - Halimat O. Sanni‐Olayiwola; Fausat L. Kolawole; Favour O. Onifade; Samson A. Oyeyinka (Future Postharvest and Food)
Abstract Obesity has reached epidemic statistics worldwide and there is an urgent need to explore more available options in addressing the condition. The potential of vegetables as natural sources of enzyme inhibitors that can regulate the progression of obesity is of great interest particularly due to possible synergistic antioxidant activities. In this study, we evaluated the phytochemical composition, antioxidant activities, and in vitro enzyme inhibition properties of selected vegetables as influenced by sun and cabinet drying methods. While a significant increase was observed in the phytochemical composition of most of the vegetables, the two drying methods had varying effects on all parameters. Cabinet drying yielded higher saponin (2.86–4.67 mg/100 g), phenolics (19.30–57.02 mg/100 g), and alkaloids (31.58–37.61 mg/100 g) contents while sun drying gave better results for flavonoids (88.13–234.15 mg/100 g). The DPPH (11.45%–29.61%) and ABTS (22.70%–35.48%) antioxidant activities varied significantly. Cabinet‐dried cabbage and sun dried carrot flours displayed the highest inhibition against alpha amylase and pancreatic lipase, respectively. A strong positive correlation was observed between phenolics and amylase inhibition and also between saponin and pancreatic lipase inhibition. Consequently, vegetable flours could serve as versatile products for the therapeutic management of obesity and related diseases.